SIFAT FUNGSIONAL PRODUK INTERAKSI FRAKSI GLOBULIN 7S KOMAK (Dolichos lablab) DAN GUM XANTAN [Functional Properties of the Interaction Product Between Globulin of 7S Fraction of Lablab Bean (Dolichos lablab) with Xantan Gum] - . Sukamto; . Aulanni’am; . Sudiyono (Jurnal Teknologi dan Industri Pangan, 2009)
Lablab bean (Dolichos lablab) seeds is a potential source of protein globulin.The bean’s protein content is 20.86 %, and the amount of globulin was more than 60% from the total protein, having major fractions of 7S and 11S. The objectives of this research were to explore the 7S globulin fractions,  to study interaction between 7S globulin fractions with xanthan gum, and to observe the functional properties of the product of the interaction. The research was conducted in 2 steps. The first step was to fractionate the 7S fractions from globulin. The second steps was to interact 7S globulin fraction with xanthan gum. The yield of these interaction were examined for its physicochemical and functional properties. The results showed that the 7S globulin fractions could be interacted by xanthan gum at pH 7. The interacted product of globulin 7S fraction 10 % with xanthan gum 0,75 % had good functional properties than globulin 7S fraction,  such as oil holding capacity, foaming capacity, and emulsion activity. Water holding capacity could not be detected because the yield became soluble. However,the foaming and emulsifying stability were still lower than those of soybean protein isolates. The research concluded that xanthan gum could be used to improve the physicochemical and functional properties of globulin 7S fraction.